Suicidal behaviour issues – crisis intervention - Zawadzki, Łukasz; Zawadzka, Agnieszka; Dębska, Agnieszka (Journal of Education, Health and Sport, 2018)
Introduction. Suicide is a serious problem globally. More and more people are dying because of taking their lives. This tragic act is an expression of helplessness and loneliness of a man who did not receive help in a timely manner. Suicide is a process of intertwined thoughts and deeds. This process lasts for several weeks to several months or even years, and the sequence of reactions taking place during that time is called suicidal behavior. This process can be interrupted at any time through crisis intervention saving human life. Aim. The aim of this work is to analyze the suicidal crisis and the phenomenon of suicide, as well as to familiarize the reader with risk factors that may indicate the possibility of committing suicide. Moreover, the aim of the work is to present effective crisis intervention to people threatened with a suicidal act. Summary. Human life is the most important value. Each saved life is a great success for both the suicide, his relatives and the whole society. That is why prevention and education are so important. If the society is sensitive to risk factors that may indicate a threat of committing suicide, it will be able to react at the right time by helping a person who is in a suicidal crisis.